High-Frequency Rheological and Piezo-Voltage Waveform Characterization of Inkjet-Printed Polymer-Based Dopant-Source Inks - Zulkifl Hussain; Zohreh Kiaee; Milad Nazarzadeh; Christian Reichel; Sebastian Tepner; Tri Tuladhar; Mike Jahn; Roman Keding (Micromachines, 2022)
This work focuses on developing an understanding of the rheological properties of polymer-based dopant-source inks at the timescales relevant to inkjet printing and their corresponding roles in determining the production of defect-free droplets. Ink-specific optimization of printing processes for phosphorus and boron dopant-source inks with different compositions is demonstrated. Rheological flow curves measured by a piezo axial vibrator (PAV) were used to study the changes in complex viscosity (η*) and in the elastic (G′) and viscous (G″) components of the shear modulus (G*) with respect to changes in frequency (from fmin = 1 kHz to fmax = 10 kHz) to obtain an insight into the high-frequency behaviour of inks, as well as the effects of temperature (25 °C and 45 °C) and the natural aging time of the inks. Inks demonstrating complex viscosity η*min ≥ 2 mPas to η*max ≤ 20 mPas and an elastic modulus G′ ≤ 20 Pa, produced droplets with negligible defects. Of the three rheological parameters (η*, G′ and G″), the elastic component (G′) of the shear modulus was observed to have the greatest significance in determining the stability and homogeneity of ink droplets, thus dictating the quality of the printed structures. The reliability and stability of droplet formation were further investigated through voltage waveform simulation using an oscilloscope.